Manipulating Lexical Forms with the PyLexibank FormSpec (Computer-Assisted Language Comparison in Practice: Tutorials on Computational Approaches to the History and Diversity of Languages, 2025)
Multilingual lexical data is typically stored in a wide variety of forms, based on many idiosyncratic decisions that vary from dataset to dataset. Here, a simple but efficient solution for the manipulation of lexical data in multilingual wordlists will be introduced. This solution, the PyLexibank FormSpec, was originall developed for the conversion of various kinds of lexical data to Cross-Linguistic Data Formats, but it can also be used as a standalone. This study offers a basic tutorial that illustrates how the FormSpec can be put to concrete use.
Keywords: PyLexibank; Lexibank; FormSpec; code; tutorial